5-azacytidine pre-treatment alters DNA methylation levels and induces genes responsive to salt stress in kenaf (Hibiscus cannabinus L.). (May 2021) - Li, Zengqiang; Hu, Yali; Chang, Mengmeng; Kashif, Muhammad Haneef; Tang, Meiqiong; Luo, Dengjie; Cao, Shan; Lu, Hai; Zhang, Wenxian; Huang, Zhen; Yue, Jiao; Chen, Peng
Abstract: Soil salinization is becoming a major threat to the sustainable development of global agriculture. Kenaf is an industrial fiber crop with high tolerance to salt stress and could be used for soil phytoremediation. However, the molecular mechanism of kenaf salt tolerance remains largely unknown. DNA methylation is an important epigenetic modifications phenomena and plays a key role in gene expression regulation under abiotic stress condition. In the present study, the kenaf seedlings were pre-treated or not with 50 μM 5-azacytidine (5-azaC, a DNA methylation inhibitor) and then subjected to different concentrations of NaCl. Results showed that the biomass and antioxidant activities (superoxide dismutase, peroxidase and catalase) of kenaf seedlings pre-treated with 5-azaC were significantly increased, while the contents of superoxide anion (O2 − ) and malondialdehyde (MDA) were decreased, indicating that 5-azaC pre-treatment could significantly alleviate salt stress injury. Furthermore, the methylation-sensitive amplified polymorphism (MSAP) analysis revealed that DNA methylation level of keanf seedlings pre-treated with 5-azaC significantly decreased. The expression of seven differentially methylated genes responsing to salt stress was significantly changed from real-time fluorescent quantitative (qRT-PCR) analysis. Finally, knocked-down of the l -ascorbate oxidase ( L-AAO ) gene by virus-induced gene silencing (VIGS) resulted in increased sensitivity of kenaf seedlings under salt stress. Overall, it was suggested that 5-azaC pre-treatment can significantly improve salt tolerance in kenaf by decreasing ROS content, raising anti-oxidant activities, and regulating DNA methylation and expression of stress-responsive genes. Highlights: Salt stress increased DNA methylation level in kenaf. 5-azaC pretreatment improved kenaf salt tolerance. 5-azaC pretreatment decreased DNA methylation and changed physiological indexes. 5-azaC altered the methylation and thus activated salt-tolerant genes expression. VIGS analysis suggested L-AAO gene positively regulates the salt resistance in kenaf.